2021
DOI: 10.1108/jd-01-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Health information-seeking behavior in the time of COVID-19: information horizons methodology to decipher source path during a global pandemic

Abstract: PurposeTo determine the differences, as represented by information horizons mapping, in the health information-seeking behavior from a group of participants between March 2019 and April 2020 of the novel coronavirus pandemic.Design/methodology/approachIn March 2019, the author conducted a study on health information-seeking behavior in which 149 participants drew information horizons maps in a health-related context. They also took health and information literacy assessments. This exact study was replicated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Information use has formed a key theme within COVID-19 research, including help and health seeking behaviours (Zhao et al , 2020; Zimmerman, 2021), the information sources that people used to adjust to COVID-19 (Bray et al , 2021; Chandler et al. , 2021; Chen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Information use has formed a key theme within COVID-19 research, including help and health seeking behaviours (Zhao et al , 2020; Zimmerman, 2021), the information sources that people used to adjust to COVID-19 (Bray et al , 2021; Chandler et al. , 2021; Chen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information use has formed a key theme within COVID-19 research, including help and health seeking behaviours (Zhao et al, 2020;Zimmerman, 2021), the information sources that people used to adjust to COVID-19 (Bray et al, 2021;Chandler et al, 2021;Chen et al, 2021;Gerosa et al, 2021;Mohammed et al, 2021;Savolainen, 2021;Thomas et al, 2021;Wang et al, 2021) and coronavirus health literacy (Bray et al, 2021;Okan et al, 2020;Sykes et al, 2021). Emerging from a variety of research traditions, including health, sociology and childhood studies, these studies have noted the vital importance of official media in the initial stages of the pandemic, with Lupton and Lewis (2021) and Sykes et al (2021), which formed two of the few qualitative studies, observing how this period was followed by a lessening of engagement with information.…”
Section: Literature Review 41 Covid-19 Researchmentioning
confidence: 99%
“…Worries and anxiety did not influence CISB in our sample. Zimmerman [ 17 ] showed that during the pandemic people were more likely to use news for health information and to use a higher number of information sources, compared to the period preceding the pandemic. Several sources that report news were often used for CISB in our sample, including newspapers, TV, radio and portals.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific evidence in a wide range of health fields shows that health literacy is associated with health-related knowledge, behaviors and ultimately health care access [ 15 ] and health outcomes [ 16 ]. In the context of the COVID-19 pandemic, health literacy can affect the approaches used to obtain information on the disease [ 17 ]. Inadequate health literacy could result in a poorer understanding of the risks associated with COVID-19, its preventive measures and symptoms, as well as in a higher possibility for misinformation, distrust in health authorities and ultimately adverse mental and physical health outcomes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studying people's information seeking behaviors amid the COVID-19 has become an urgent research topic in the latest LIS literature (Ali et al, 2020;Kelly et al, 2020;Li and Zheng, 2020;Moreno et al, 2020;Superio et al, 2021;Zimmerman, 2021). While some of these studies focus on older adults, only a handful to date have focused on older adults from a non-healthspecific perspective.…”
Section: Studies Of Information Sources During Public Health Crisesmentioning
confidence: 99%